Effect of Omeprazole to Dyspeptic Symptom on Ramadan Fasting Patient based on Dyspepsia Symptoms Severity Index Scores - Eddy Chandra; Suzanna Ndraha; IDN Wibawa (The Indonesian Society for Digestive Endoscopy, 2013)
Background: Dyspepsia is a symptoms collection of discomfort at the upper abdomen. Ramadan Fasting is a worship that must be run by all Moslems that do not eat and drink for ± 12 hours. Proton pump inhibitors are drugs commonly given to patients with dyspepsia with mechanism controlling gastric acid secretion. The aim of this study is to find the effect of omeprazole to the patient with dyspepsia and undergo Ramadan fasting.Method: Using analytic study design, conducted in outpatient in Koja Hospital Jakarta from June - July 2013, for patients with dyspepsia who will undergo Ramadan fasting. Subjects are divided into 2 groups; one group was given omeprazole while others were given a placebo. Before and after 2 weeks of fasting, dyspepsia symptoms severity index scores (DSSI) was taken which assessed changes in both groups and compared using student T-test.Results: DSSI scores on average before the intervention of both groups (n = 30) was not significant (p = 0.9). In the placebo group obtained increasing of DSSI score from 27.7 ± 14 to 36 ± 14.8 (p = 0.001), whereas in the omeprazole group obtained increasing of score only from 27.2 ± 9.4 to 30 ± 9.9 (p = 0.08). In the placebo group score worsened by 8.3 ± 7.2 but in the omeprazole group with only 2.7 ± 5.7 (p = 0.02).Conclusion: There was a significant decrease of DSSI scores in fasting patient with omeprazole. Therapy with omeprazole 20 mg twice daily during the month of fasting can reduce the abdominal complain in patient with dyspepsia.Keywords: dyspepsia, DSSI, fasting, Ramadan